Measure of Early Vision Use: initial validation with parents of children with cerebral palsy. Issue 15 (17th July 2022) - Deramore Denver, Belinda; Froude, Elspeth; Rosenbaum, Peter; Imms, Christine
Abstract: Purpose: To report initial psychometric evidence on the Measure of Early Vision Use. Method: Data on performance of the Measure of Early Vision Use scale were collected from 100 parents of children with cerebral palsy aged 0–12 years via online survey. Psychometric evaluation included assessment of scale dimensionality using Classical Test Theory and hypothesis testing for evidence of construct validity. Results: Principal components analysis of the 14-item parent-rated Measure of Early Vision Use revealed one component with an eigenvalue of 9.343, explaining 66.7% of variance; internal consistency was high (Cronbach's α = 0.96). Total scores ranged from 15–56 (Mean 42.8, standard deviation = 10.6). The results support seven pre-defined hypotheses including statistically significant differences in MEVU-total scores between children with and without parent-reported cerebral visual impairment. Conclusions: Measure of Early Vision Use is the first assessment tool to describe 'how vision is used' in children with cerebral palsy. Results provide preliminary evidence that the measure comprises a unidimensional construct, sufficient construct validity, and feasibility as a parent-completed online assessment. Findings on internal structure provide foundational evidence and require further testing with Confirmatory Factor Analysis or Rasch Analysis. IMPLICATIONS FOR REHABILITATION: The Measure of Early Vision Use is a new instrument to describe the use of basic visual abilities and is feasible to use as a parent-completed online questionnaire. The Measure of Early Vision Use is a unidimensional scale with sufficient construct validity to supports its use as a measure of 'how vision is used' without confounding visual ability with the reason why it might be impaired (e.g., cerebral vision impairment, motor limitations, or cognition). There is potential for the Measure of Early Vision Use to support early intervention planning for children with (or at high risk of) cerebral palsy.